Yoga and Exercise for Fetal Heart Rate, Body Mass Index, And Blood Pressure of Antenatal Mothers: Life Sciences- Nursing - Sathiyabama, G.; Kalabarathi , Dr.S .; Nidhisharma, Dr. (International Journal of Life Science and Pharma Research, 2023)
oga is a traditional practice with Indian roots that has many therapeutic benefits. Pranayama and dhyana on bodymass index (BMI) and mean blood pressure (MBP) of the antenatal mother (AM) and fetal heart rate (FHR) are critical for theantenatal mothers. Our aim is to determine Asana's impact in antenatal mothers. This Single blinded placebo-controlled trial wasconducted at Saveetha Medical College and Hospital, Chennai, India. Consecutive sampling was used to select the samplesconveniently. Then, they were randomly assigned into four groups using a random number table: control (CN), yoga group (YG),and Antenatal exercise group (EG), and Yoga and Antenatal exercise group (YAE) with 33 samples in each group. The CN groupreceived conventional management, the YG and EG groups received Yoga intervention and antenatal exercises, respectively, andthe YAE group received both Yoga and antenatal. The groups received their respective treatment 2 days a week for 16 consecutiveweeks. BMI, BP of the AMs, and FHR were assessed at the end of the 4th week, 8th week, 12th week, and 16th week. A total of 132samples accounted for the study results, which showed that the YAE group subjects performed significantly better than the YG,EG, and CN groups in all temporal outcomes (P<0.001). The CN group subjects did not progress significantly compared to theYG and EG group samples. The study concluded that instead of using Yoga as an individual tool in the training AM, addingantenatal exercise will be more beneficial in normalizing BMI, BP, and FHR among AMs.